PERAN KOPERASI UNIT DESA (KUD) DALAM MENINGKATKAN PRODUKTIVITAS KELOMPOK TANI DI DESA TANAH HABANG KANAN KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Handayani, Ramona; Rahmadania, Rahmadania (Inovatif Jurnal Administrasi Niaga, 2020)
Village Unit Cooperatives (KUD) were formed on the basis of common perceptions and farmers' needs for the ease of obtaining agricultural production facilities and infrastructure by basing their activities on the principles of cooperatives as well as as a people's economic movement based on the principle of kinship. In the future, the role of cooperatives in Indonesia is expected to remain even more important, especially in relation to being a vehicle for the development of the people's economy, however cooperatives will also face increasingly tough challenges. Globalization, socio-economic development of society and the development of cooperatives themselves will require cooperatives to be able to increase their business roles and functions if they do not want to be left out by other business actors. In KUD Tanah Habang Village, there was a problem of lack of community interest in becoming cooperative members, lack of training and information provided and insufficient stock of farming equipment needed. Based on the above, this study aims to determine the role of the Village Unit Cooperative (KUD) in increasing the productivity of farmer groups in Tanah Habang Kanan Village, Kec. Lampihong Kab. Balangan, the obstacles faced by the Village Unit Cooperative (KUD) in increasing the productivity of farmer groups in Tanah Habang Kanan Village, Kec. Lampihong Kab. Balangan and the Efforts Made to Improve the Village Unit Cooperative of Tanah Habang Kanan, Paringin District, Balangan Regency. The research approach used a qualitative approach. The results show that the role of KUD in Tanah Habang Kanan village is quite optimal even though there are some indicators that are still less than optimal, such as fulfilling the needs of farmers' tools, which are still lacking due to lack of coordination with the agricultural department, and lack of skills and training given to farmers. and cooperatives do not help in overcoming unemployment due to the lack of information on cooperative programs. The obstacles faced include: inadequate additional farming tools as well as inadequate skills development and training due to lack of coordination with the Department of Agriculture, as well as a lack of information or socialization so that there is still a minimum of enthusiasts. Efforts made in overcoming obstacles include: increasing the counseling carried out by the cooperative to the community, especially regarding cooperative programs in farming, and increasing coordination with the agriculture agency so that the role of cooperatives has more power.